Impact of SO2 and bentonite addition during fermentation on volatile profile of two varietal white wines - Almeida Santos, Cátia (2020)
To understand the impact of SO2 and ascorbic acid (AA) in must fermentation, Arinto and Síria musts were fermented under the same conditions, but in the presence of different doses of SO2 and with or without bentonite addition. Arinto was fermented with 0, 50, 100 mg/L of SO2 and 100mg/L of AA. Síria was fermented with 0, 15, 30, 45 mg/L of SO2 and 100 mg/L of AA. The volatile organic compounds (VOCs) were analysed by HS-SPME-GC/MS. Based on PCA results obtained from VOCs profiles for both varieties, first and second principal components were responsible for more than 60% of the respective system´s variance. In both wines, the presence or absence of bentonite was clearly discriminated. This work also shows that depending on the different doses of SO2 used, the resulting VOC profiles clearly discriminate these different fermentation conditions. The use of AA in both varieties resulted in a different VOC profile compared to the use of SO2. From this study It was also possible to verify from the VOCs profile, that Arinto wine is less resilient to fermentation changes then Síria wine, which may impact technological choices